WHO WANTS TO WORK LONGER? - Strasburger, Aleksander; Zajkowska, Olga (Metody Ilościowe w Badaniach Ekonomicznych, 2013)
The observed collapse of demographic pyramid increases the tension on the social security systems, especially pensions. It implies a requirement to extend the retirement age. On the basis of Eurobarometer 65.1 we calculate difference between expected and preferred retirement age in Poland. Then we show the determinants of individual differences. Particular attention is paid to the problem of non-random missing observations.